Hindu Architecture
In Manasara Silpa-Sastra certain discrepancies in the book made me to investigate. This book is the result to investigate. This book is the result of author investigation lasting over a period of several years. This book deals with fourteen chapters like. First chapter is introductory second chapter is determination of the Cardinal points third chapter is Hindu system of surveying, fourth chapter is hindu measurements, fifth chapter is hindu proportions or the relation between length and breadth, sixth chapter is the perimeter and the yoni, seventh chapter is tests for measurements, eighth chapter is hindu fractions and limilting values. Ninth chapter is the sacrificial altars, Tenth chapter is town planning, Eleventh chapter is house planning. Twelfth chapter is sculpture, Thirteenth chapter is about Silpis who are they?.